AccessAnesthesiology: A Resource Description. Issue 3 (2nd October 2019) - Rickelman, Mary C.
Abstract: AccessAnesthesiology from McGraw-Hill is an interactive database platform that provides user access to electronic books, quick reference material, drug monographs, multimedia, sample cases, and anesthesia study tools for the board review. It is a database for medical students, nurse anesthetist students, residents, and others in the health care field interested in anesthesia. This article will provide an overview of the features found in this online tool. Layout, resource tools, searching options, and navigation will be shared in addition to unique features in AccessAnesthesiology.